Update on the Role of the Endothelial Glycocalyx in Angiogenesis and Vascular Inflammation - Hu, Zhengping; Cano, Issahy; D’Amore, Patricia A. (Frontiers in Cell and Developmental Biology, 2021)
The endothelial glycocalyx is a negatively charged, carbohydrate-rich structure that arises from the luminal surface of the vascular endothelium and is comprised of proteoglycans, glycoproteins, and glycolipids. The glycocalyx, which sits at the interface between the endothelium and the blood, is involved in a wide array of physiological and pathophysiological processes, including as a mechanotransducer and as a regulator of inflammation. Most recently, components of the glycocalyx have been shown to play a key role in controlling angiogenesis. In this review, we briefly summarize the structure and function of the endothelial glycocalyx. We focus on its role and functions in vascular inflammation and angiogenesis and discuss the important unanswered questions in this field.